Lycium barbarum Polysaccharide Prevents Cisplatin Induced MLTC-1 Cell Apoptosis and Autophagy via Regulating Endoplasmic Reticulum Stress Pathway [Retraction] - Yang F; Wei Y; Liao B; Wei G; Qin H; Pang X; Wang J (Dove Medical Press, 2022)
Yang F, Wei Y, Liao B, et al. Drug Des Devel Ther. 2018;12:3211–3219. The Editor and Publisher of Drug Design, Development and Therapy wish to retract the published article. Concerns were raised following the authors request to change western blot data in Figure 4D. The authors provided a replacement image for Figure 4D, however they failed to adequately explain why they wished to change the images. In addition, the authors could not provide the original data for the western blots shown in Figure 4D or for any of the other western blot images shown in Figures 2A and 3C. It was determined the findings reported in the article were unreliable and a retraction was requested. The authors were notified of this decision. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted.” This retraction relates to this paper